A sobemovirus hindering the utilization of Calopogonium mucunoides as a forage legume in the lowland tropics - Morales, Francisco José; Castaño, M.; Arroyave, José A.; Ospina, M.D. (Scientific Societies, 1995)
The cultivation of calopo, Calopogonium mucunoides, as a promising forage legume for the lowland tropics, was hindered by its susceptibility to a severe yellow mosaic disease observed in the Eastern Plains of Colombia. An isometric virus ca. 28 nm in diameter was observed by electron microscopy in leaf extracts and purified preparations, and in phloem cells of systemically infected calopo plants. The virus was transmitted by mechanical means and by the chrysomelid beetle Diabrotica balteata. The host range of the virus was restricted to the legumes Phaseolus vulgaris, Vigna unguiculala, V. radiata, Centrosema spp., and Senna occidentalis. The physical and chemical properties of the calopo virus were similar to those reported for the sobemovirus group, and the virus was antigenically related to the bean and cowpea strains of southern bean mosaic virus (SBMV). However, the host range of the calopo virus differed from the pathogenicity spectra of the bean, cowpea, Ghanaian, and Mexican strains of SBMV. Nucleotide sequence analysis of a 609 bp fragment amplified from the coat protein region of the calopo sobemovirus revealed similarities of 81.8 and 66.1% with the corresponding regions of the bean and cowpea strains, respectively, of SBMV. The respective homologies increased to 83.7 and 67.8% when the deduced amino acid sequences of these viruses were compared. It is concluded that the mosaic disease of calopo is caused by a previously undescribed sobemovirus for which the name calopo yellow mosaic virus is suggested.